336WASIAT WAJIBAH SEBAGAI PENEMUAN HUKUM OLEH HAKIM DALAM PERKARA WARIS BEDA AGAMA (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 16 K/AG/2010) - Gani, Nurhadi Abdul (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2017)
The majority practice of inheritance distribution in the Religious Courts for the heirs of different religions was the nonmuslim heirs are not entitled to the inheritance of their parents, such a verdict is not without a strong foundation, there is a strong basis utterance of Prophet Muhammad SAW which states: “muslim does not inherit a nonmuslim, and a nonmuslim also does not inherit a Muslim